A new concept of advanced management of hazardous waste in the Republic of Korea. Issue 11 (November 2019) - Choi, Hyeong-Jin; Choi, Yong; Rhee, Seung-Whee
In order to activate the recycling of hazardous wastes, the hazardous characteristics of wastes should be removed or stabilized. However, most recyclers in recycling companies do not understand how to remove the hazardous characteristics in wastes with the proper technology. The aim of a new form of advanced management of hazardous waste is to inform recyclers and operators in industries about hazardous characteristics and the treatment methods required for all management processes, from waste generation to final treatment. In a new method of advanced management of hazardous wastes, chemicals in the waste should be initially examined at the generation source in each industry to create a chemical catalogue. Since hazardous characteristics can be determined by a chemical catalogue obtained from the waste, the hazardous characteristics of wastes can be established and considered when choosing the proper treatment method. Then, the categories of waste treatment methods for each hazardous characteristic can be introduced for generators to treat hazardous wastes properly. Therefore, it is possible to create a link between the source and the final treatment of hazardous wastes using a new concept of industry (In), waste (W), hazardous chemicals and their hazardous characteristics (Ha) and treatment methods (T). This new concept of the "InWhat" system, which includes all management processes in Korea, from waste generation to final treatment, will be proposed as a tool in the advanced management of hazardous wastes.